2019
DOI: 10.1093/tbm/ibz134
|View full text |Cite
|
Sign up to set email alerts
|

The systematic cultural adaptation of a UK public health cancer awareness raising programme for Malaysia: the Be Cancer Alert Campaign

Abstract: We used a cultural adaptation framework and local partnership working in Malaysia to translate and implement an established cancer awareness-raising mass media campaign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Arguably, the BCAC-CRC study is one of the most robust evaluations of public health efforts to improve early cancer detection in an Asian country, particularly in the form of a cancer mass media campaign, despite the limitations that we have noted above [10]. Overall, the findings of the evaluation indicate that a culturally adapted, evidence-based mass media intervention [14] appears to impact positively in terms of improving CRC symptom awareness among an Asian population; and that impact is more likely when a campaign operates a differentiated approach that matches modes of communication to the ethnic and religious diversity in a population. Therefore, further research is needed to identify which communication channels and form of tailoring are required to reach (in the example of Malaysia) the Chinese community, people without formal education and older people.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Arguably, the BCAC-CRC study is one of the most robust evaluations of public health efforts to improve early cancer detection in an Asian country, particularly in the form of a cancer mass media campaign, despite the limitations that we have noted above [10]. Overall, the findings of the evaluation indicate that a culturally adapted, evidence-based mass media intervention [14] appears to impact positively in terms of improving CRC symptom awareness among an Asian population; and that impact is more likely when a campaign operates a differentiated approach that matches modes of communication to the ethnic and religious diversity in a population. Therefore, further research is needed to identify which communication channels and form of tailoring are required to reach (in the example of Malaysia) the Chinese community, people without formal education and older people.…”
Section: Resultsmentioning
confidence: 85%
“…The results of the evaluation, overall, indicated that symptom awareness improved after campaign delivery and that, more specifically, prompted awareness about all CRC symptoms improved among participants who saw any of the BCAC-CRC materials and did not recognise the symptoms as baseline, compared to participants who did not recall seeing or hearing the campaign. This post-campaign increase in awareness may be related to the way in which the campaign materials were adapted and presented [14] and informed by best available evidence [10]. For example, print advertisements that highlighted the colon/rectum and the radio advertisements that emphasised paying attention to bowel habits were adapted to suit the multi-ethnic population and culture of Malaysia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are confident in the power of knowledge to nudge populations towards better habits, supported by several awareness-raising campaigns that in recent years generated significant results in terms of improving general health [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Awareness improved significantly at follow-up for three prompted BC symptoms, whereas awareness about all prompted CRC symptoms was improved. The success of the BCAC-BC was due partly to the systematic cultural adaptation process 18 that was undertaken in order to address, for example, the need to refer to breast-related issues with contextual sensitivity and to include only information about a lump. Although a lump appeared already to be a commonly known symptom, it was unacceptable culturally to present other symptoms of BC.…”
Section: Discussionmentioning
confidence: 99%